Relationship of swim performance to upper body strength and power in collegiate level sprint swimmers - Burgos, Joaquin Miguel E. (College of Human Kinetics, University of the Philippines Diliman, 2019)
The correlation between the upper body strength, and upper body power to the swim performance of fifteen (15) UP varsity swim team athletes were assessed with the use of the maximum repetition lat pulldown test, the resistance pulley test for strength and power, respectively. The strength test consisted execution of repetitions of a concentric lat pulldown with an initial weight of 10-kilograms (kg) which further increased after every successful repetition. The average weight lifted by the 15 athletes was 80.33-kg, with a standard deviation of 7.67. The power test was done by using a resistance pulley connected to a linear positional transducer which measured the power generated with each pull. The results showed an average of 213.87 watts (W), with a standard deviation of 56.30. Swim performance data was collected on the second day of testing by timing 50-meter (m), and 100-m swim sprints using the resistance pulley. The 50-m sprint resulted in a 26.01-seconds (s) average, and a 1.20 standard deviation, while the 100-m sprint showed an average of 57.21-s, with a standard deviation of 2.74. Using Spearman's rank-order correlation at 0.10 level of significance, upper body strength and swim performance at 50-m, and 100-m coefficients were -0.48183, and -0.25240, respectively with p-values of 0.0690, and 0.3641, respectively. This showed a moderate negative monotonic association and a significant correlation with upper body strength, and swim performance at 50-m only. The upper body power and swim performance correlation was observed in 50-m, and 100-m sprints with coefficients of -0.61429, and-0.51342, respectively, and p-values of 0.0503, respectively. This showed a moderate negative monotonic association, and a correlation of upper body power in both 50-m, and 100-m. sprints. The data shows that although both strength and power have a significant correlation to swim performance, power is a stronger predictor in shorter distances.